+0

# if 1=2 2=10 3=30 4=68 then 5=?

0
922
5

if 1=2 2=10 3=30 4=68 then 5=?

Guest Jul 23, 2014

#2
+91446
+10

$$\begin{tabular}{|c|c|c|c|c|c|} \hline x&1&2&3&4&5\\\hline f(x)&2&10&30&68&\\\hline \end{tabular}$$

Okay they are not getting bigger by a set multiplication factor - as the x gets bigger, f(x) gets MUCH bigger.

Try squared, no still not big enough -- Try cubed.  That looks close.  Add x and you've got it.

$$\begin{tabular}{|c|c|c|c|c|c|} \hline x&1&2&3&4&5\\\hline f(x)&2&10&30&68&\\\hline x^2&1&4&9&16&\\\hline x^3&1&8&27&64&\\\hline x^3+x&2&10&30&68&\\\hline \end{tabular}$$

$$\\f(x)=x^3+x\\\\ f(5)=5^3+5=125+5=130$$

Melody  Jul 23, 2014
Sort:

#1
+18827
+5

if     1  =  2

2 = 10

3 = 30

4 = 68

then 5 =   ?

$$\begin{array}{ccccc} n+1& p(n)& \Delta_1 & \Delta_2 & \Delta_3 \\ \\ 1&2& \\ &&8\\ 2&10&&12 \\ &&20&&{6}\\ 3&30&&18&\downarrow \\ &&38&&({6})\\ 4&68&&(24) \\ &&(62)\\ 5&(130)& \end{array}$$

5 =   130

### Polynom

$$p(n) = n^3+3*n^2+4*n+2 \quad | \quad n = 0,1,2,3, ...$$

heureka  Jul 23, 2014
#2
+91446
+10

$$\begin{tabular}{|c|c|c|c|c|c|} \hline x&1&2&3&4&5\\\hline f(x)&2&10&30&68&\\\hline \end{tabular}$$

Okay they are not getting bigger by a set multiplication factor - as the x gets bigger, f(x) gets MUCH bigger.

Try squared, no still not big enough -- Try cubed.  That looks close.  Add x and you've got it.

$$\begin{tabular}{|c|c|c|c|c|c|} \hline x&1&2&3&4&5\\\hline f(x)&2&10&30&68&\\\hline x^2&1&4&9&16&\\\hline x^3&1&8&27&64&\\\hline x^3+x&2&10&30&68&\\\hline \end{tabular}$$

$$\\f(x)=x^3+x\\\\ f(5)=5^3+5=125+5=130$$

Melody  Jul 23, 2014
#3
+91446
0

Heureka, you have got the same answer as me but I don not understand what you have done.

Melody  Jul 23, 2014
#4
+18827
+5

Hi Melody,

this is a arithmetic succession. Order is 3 ( So i hold 6 as a constant number in Delta 3 so the order is 3 ). I got the Polynom from Internet.

Beginning bei n= 0. If i set x = n+1 so the Polygon can written as:

$$p(x) \\ = (x-1)^3+3(x-1)^2+4(x-1)+2 \\ = x^3-3x^2+3x-1+3(x^2-2x+1)+4x-4+2 \\ = x^3-3x^2+3x-1+3x^2-6x+3+4x-4+2\\ = x^3-3x^2+3x^2+3x-6x+4x -1+3-4+2\\ = x^3+x \\ p(x)=x^3+x \quad | \quad x=1,2,3,... \quad Your\quad solution$$

heureka  Jul 23, 2014
#5
+91446
0

Thanks Heureka

Melody  Jul 23, 2014

### 15 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details